RISIKO MAKRO EKONOMI DAN PENGARUHNYA TERHADAP NET INTEREST MARGIN BANK DI INDONESIA (STUDI PADA SEKTOR PERBANKAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA TAHUN 2008 – 2017) - Rahayu, Leni Putri; Sumarto, Agus Herta (Teropong : Jurnal Manajemen dan Bisnis, 2021)
This study aims to analyze the effect of macroeconomic risk on the Bank's neit interest margin. The population in this study were 25 banks listed on the Indonesia Stock Exchange. The sample used was 25 banks. Data collection method that is using the method of documentation from the internet media. The data analysis method uses the Fixed Effect Model (FEM). This study proves that statistically Economic Growth Risk and SBI Interest Rate Risk affect the Bank's Net Interest Margin. Whereas Inflation Risk and Exchange Rate Risk statistically have no effect. For overall, this model cannot explain the effect of macroeconomic risk on the bank's net interest margin.